Examination of the Role of Mitochondrial Morphology and Function in the Cardioprotective Effect of Sodium Nitrite Administered 24 h Before Ischemia/Reperfusion Injury - Demeter-Haludka, Vivien; Kovács, Mária; Petrus, Alexandra; Patai, Roland; Muntean, Danina M.; Siklós, László; Végh, Ágnes (Frontiers in Pharmacology, 2018)
Background: We have previous evidence that in anesthetized dogs the inorganic sodium nitrite protects against the severe ventricular arrhythmias, resulting from coronary artery occlusion and reperfusion, when administered 24h before. The present study aimed to examine, whether in this effect changes in mitochondrial morphology and function would play a role. Methods: Thirty dogs were infused intravenously either with saline (n=15) or sodium nitrite (0.2 µmol/kg/min; n=15) for 20 min, and 24h later, 10 dogs from each group were subjected to a 25 min period of occlusion and then reperfusion of the left anterior descending coronary artery. The severity of ischaemia and ventricular arrhythmias were examined in situ. Left ventricular tissue samples were collected either before the occlusion (5 saline and 5 nitrite treated dogs) or, in dogs subjected to occlusion, 2 min after reperfusion. Changes in mitochondrial morphology, in complex I and complex II-dependent oxidative phosphorylation (OXPHOS), in ATP, superoxide and peroxynitrite productions were determined. Results: The administration of sodium nitrite 24h before ischemia/reperfusion significantly attenuated the severity of ischaemia, and markedly reduced the number and incidence of ventricular arrhythmias. Nitrite also attenuated the ischaemia and reperfusion (I/R)-induced structural alterations, such as reductions in mitochondrial area, perimeter and Feret diameter, as well as the increase in mitochondrial roundness. The administration of nitrite, however, enhanced the I/R-induced reduction in the mitochondrial respiratory parameters; compared to the controls, 24h after the infusion of nitrite, there were further significant decreases, e.g. in the complex I-dependent OXPHOS (by -20% vs. -53 %), respiratory control ratio (by -14% vs. -61%) and in the P/E control coupling ratio (by 2% vs. -36%). Nitrite also significantly reduced the I/R-induced generation of superoxide, without substantially influencing the ATP production. Conclusions: The results suggest that sodium nitrite may have an effect on the mitochondria; it preserves the mitochondrial structure and modifies the mitochondrial function, when administered 24h prior to I/R. We propose that nitrite affects primary the phosphorylation system (indicated by the decreased P/E ratio), and the reduction in superoxide production would result from the subsequent suppression of the ROS producing complexes; an effect which may certainly contribute to